Genetics of phase I enzymes - Yu, Aiming (Henry Stewart Talks, 2007)
Inter-patient variations caused by Phase I drug metabolizing enzymes, Genetic polymorphism of CYP2D6 and impact on psychopharmacotherapy, Metabolism, pharmacokinetics, pharmacodynamics and toxicity, Pharmacogenetics and pharmacogenomics move towards individualized drug therapy